2005
DOI: 10.1097/01.rli.0000170818.03210.ee
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Echogenicity Characterization of Poly[lactide-coglycolide] (PLGA) Microparticles and Preliminary In Vivo Ultrasound Enhancement Study for Ultrasound Contrast Agent Application

Abstract: The 3-microm PLGA microparticles provided significant enhancement in vitro and in vivo without any toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…This development of NPs as imaging-contrast agents may also offer enhanced sensitivity and specificity for in vivo tumor imaging. For example, an in vivo study demonstrated that PLGA microparticles induced a significant enhancement of 47% intratumoral vessels detected after injection [84]. Goldberg et al developed PLGA perfluorocarbon-filled microparticles and injected them in rabbits with VX2 tumors.…”
Section: Cancersmentioning
confidence: 99%
“…This development of NPs as imaging-contrast agents may also offer enhanced sensitivity and specificity for in vivo tumor imaging. For example, an in vivo study demonstrated that PLGA microparticles induced a significant enhancement of 47% intratumoral vessels detected after injection [84]. Goldberg et al developed PLGA perfluorocarbon-filled microparticles and injected them in rabbits with VX2 tumors.…”
Section: Cancersmentioning
confidence: 99%
“…Various polymeric microbubbles have been investigated for ultrasonic imaging (Forsberg et al 2004; Lavisse et al 2005; Ketterling et al 2007; Grishenkov et al 2009a; Grishenkov et al 2009b; Lu et al 2009; Yang et al 2009; Sciallero et al 2012) and targeted drug delivery/therapeutics (Wheatley et al 2007; Jie et al 2008; Lu et al 2009; Sirsi et al 2009) (see the review by Xiong et al (Xiong et al 2011)). Specifically, PLA as well as PLGA—a block copolymer with varying lactic to co-glycolic acid ratios—has been investigated as an encapsulating material for contrast microbubbles.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo contrast-enhanced power Doppler ultrasonography evaluation on melanoma grafted mice showed 50% enhancement of detection of intratumoral vascularization after injection of 3-mm poly(lactide-coglycolide) microparticles. No toxicity was histologically observed (41).…”
Section: Contrast Agents Molecular Probes and Tracersmentioning
confidence: 99%
“…Ultrasound techniques have also been shown to be very useful in murine cancer research (38)(39)(40)(41)(42)(43)(44). Highfrequency UBM has been used for the quantitative analysis of early tumor growth in mice bearing melanoma xenografts (38).…”
Section: Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation